Optimization of Customer Flexibility within Implicit Demand Side Management Programs - Bilbiloska, Katerina; Mateska, Aleksandra Krkoleva; Krstevski, Petar (IEEE, 2022)
This paper proposes simple, yet effective solution for optimization of the use of household appliances to enable implementation of implicit Demand Side Management (DSM). The proposed optimization solution is based on prior characterization of appliances, considers the customer’s comfort requirements and the characteristics of the envisaged program. The approach ensures cost-effective and simple implementation without overburdening the aggregator/retailer and the customers with advanced technical requirements and investments. The paper includes results from sensitivity analyses that show the applicability of the solution under various constraints emerging from the preferences of the user as well as from the requirements of the implemented DSM program.
Keywords: demand side management , domestic appliances , optimisation , retailing